Study on Menorrhagia: Correlation with Fibroids (Journal of Enam Medical College, 2021)
Background: Excessive menstrual bleeding called menorrhagia is a common presentation of females seeking medical attention. Normally there is considerable variation in menstrual cycle length, duration and flow.Objective: To find out the assocation of fibroids in patients presenting with menorrhagia.Materials and Methods: This cross-sectional prospective study was done from January to June 2013 among the female patients admitted in the department of Gynaecology & Obstetrics in Dhaka Medical College & Hospital. Patients presented with the complaints of menorrhagia and treated by surgical management were included.Results: Total 96 patients were included. The age range was 28–49 years with mean age 41.08 ± 5.174 years. In 92 (46.5%) patients excessive per vaginal bleeding was noted. Pain during menstruation was another major complaint (45, 46.5%). Lower abdominal heaviness was reported in 32 patients (16.2%). In about half of the patients (49%) uterine fibroid was diagnosed. In 29 patients (30.2%) adenomyosis was the finding. Out of 47 fibroid cases 39 (83%) had per vaginal bleeding history. Only 10 patients without fibroid experienced pervaginal bleeding. Chi-squared test was done to see whether there was any association between these two variables and the result was highly significant (p